FPGA implementation of an Islanding detection technique for microgrid using periodic maxima of superimposed voltage components - Kumar, Praveen; Kumar, Vishal; Pratap, Rajendra (IET generation, transmission & distribution, 2020)
In this study, a novel islanding detection technique (IDT) based on the islanding discrimination factor using the periodic maxima of superimposed voltage components is proposed. The voltage profile of the target distributed generator is monitored continuously and its sequence components are extracted using half-angle theorem. A modular approach is used to implement the IDT algorithm, which is targeted on the reconfigurable hardware, i.e. field-programmable gate array. Hardware description language Verilog has been used to optimise the hardware resources and minimise the computational complexity. Hardware-in-loop verification of the proposed IDT has been done for islanding and non-islanding events with a microgrid (MG) test system developed on real-time digital simulator. Various cases for both islanding and non-islanding events, namely different faults are realised on the developed MG system. The results suggest that the proposed scheme successfully differentiates islanding events from a non-islanding event, and also detects the islanding event accurately under perfect power balance condition within half a cycle.